2014
DOI: 10.1590/s0100-69162014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties of the 137Cs technique for validation of soil redistribution modelling in a semiarid meso-scale watershed

Abstract: Scarcity of long-term series of sediment-related variables has led watershed managers to apply mathematical models to simulate sediment fluxes. Due to the high efforts for installation and maintenance of sedimentological gauges, tracers have been pointed out as an alternative to validate soil redistribution modelling. In this study, the 137 Cs technique was used to assess the WASA-SED model performance at the Benguê watershed (933 km²), in the Brazilian semiarid. Qualitatively, good agreement was found among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the previous example, it is likely that the Caatinga roots expanded during the 12-day gap, causing the macro porosity to have negligible influence on the initial abstractions and, as a result, runoff could be initialized under less favourable hydrological conditions. Medeiros et al (2009) argue that the influence of the interception losses in the overall water balance is roughly constant in the AEB. In the dry period, the absolute interception is negligible, as the amount of rain is very limited (average total precipitation of 50 mm accumulated from June to December, which accounts for 9% of the yearly total in the study period).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the previous example, it is likely that the Caatinga roots expanded during the 12-day gap, causing the macro porosity to have negligible influence on the initial abstractions and, as a result, runoff could be initialized under less favourable hydrological conditions. Medeiros et al (2009) argue that the influence of the interception losses in the overall water balance is roughly constant in the AEB. In the dry period, the absolute interception is negligible, as the amount of rain is very limited (average total precipitation of 50 mm accumulated from June to December, which accounts for 9% of the yearly total in the study period).…”
Section: Resultsmentioning
confidence: 97%
“…Among the main reasons for the low runoff coefficient at AEB, there are high potential evapotranspiration rates (fivefold the precipitation annually), high infiltration rates associated with deep water table and vegetation interception. In fact, Medeiros et al (2009), studying the Caatinga in the AEB in the period 2004-2008, concluded that 12% of the rainfall (26 times the runoff) consisted of forest interception losses, caused mainly by the high evaporation rate, despite the vegetation low canopy-trunk storage capacity (0.58 mm). For the events with precipitation above 10 mm, interception losses account for 11% on average, with coefficient of variation of 0.7.…”
Section: Resultsmentioning
confidence: 99%
“…de Araújo, Pinheiro, Medeiros, de Figueiredo, and Bronstert (2018) monitored a 68 m 2 hillslope in the semiarid Aiuaba Experimental Basin for 4 years and concluded that gross erosion there was 2 Mg ha −1 yr −1 , the same value measured by dos Santos et al (2017) in a hilly 1-ha area also in North-east Brazil. Medeiros, de Araújo, and Andrello (2014) used Caesium-137 to measure long-term gross erosion in a preserved 24-ha hillslope in the same region and concluded that it was 1 Mg ha −1 yr −1 . In humid Southeast Brazil, Mendes, Mahler, and de Andrade (2011) measured erosion rates in mountainous experimental hillslopes (88 m 2 ) with values ranging from 10 (fallow) to 30 (annual crops) Mg ha −1 yr −1 , much lower than in Gilbués, although slope steepness was much higher (65% in the former against 20% in the latter).…”
Section: Measurements At the Hillslope Scalementioning
confidence: 99%
“…At the scale of experimental plots or transects, many studies have been made in areas cultivated with grain crops submitted to different systems of soil use and management (Fraga and Salcedo, 2004;Arthur et al, 2007;Santos and Sparovek, 2011), sugarcane (Sparovek et al, 2000; Rev Bras Cienc Solo 2021;45:e0210089 Bacchi et al, 2003;Pires et al, 2009b;Bacchi et al, 2011), pasture (Bacchi et al, 2003;Fraga and Salcedo, 2004), forest (Andrello et al, 2009), and used for mineral extraction (Minella et al, 2014). In hydrographic micro basins, the 137 Cs fallout technique were used in studies carried out in Piracicaba (SP) by Bacchi et al (2003) and Guimarães et al (2003), in Aiuapaba (CE) by Medeiros et al (2014), in the Mato Frio stream region (RS) by Minella et al (2014), in Arvorezinha (RS) by Didoné et al (2019), and in the Pampa region (RS) by Valente et al (2020).…”
Section: Laboratory/fieldmentioning
confidence: 99%
“…The technique has also been applied in other types of permanent preservation areas, such as lakes, estuaries, and steep slopes aiming to analyze erosion and sedimentation processes (Saito et al, 2001;Figueira et al, 2006;Neves et al, 2014;Carvalho et al, 2016), to map the radioactivity distribution (Ribeiro et al, 2017), and to monitor the environmental pollution (Cunha et al, 1999). Adequate results in sediment redistribution studies (Table 3), have turned the 137 Cs fallout technique effective for the validation of empirical and physical models such as the Universal Soil Losses Equation (USLE) and the Water Erosion Prediction Project (WEPP) (Sparovek et al, 2000;Bacchi et al, 2003Bacchi et al, , 2011, the Nutrient Monitoring Model (NUTMON), used to assess the balance of nutrients in the coffee crop (Araújo et al, 2009), and the Model of Water Availability in Semiarid Environments with Sediment Dynamics Component (WASA SED) (Medeiros et al, 2014).…”
Section: Laboratory/fieldmentioning
confidence: 99%